'I felt like I was doing something wrong': A qualitative exploration of mothers' experiences of breastfeeding. (2nd April 2019) - Jackson, Jessica Eve; Hallam, Jenny
Abstract : Despite its multiple health benefits, rates of breastfeeding to 2 years and beyond remain low in the UK. This qualitative study explored the experiences of support provided by health professionals to mothers breastfeeding beyond infancy. A key finding of the study was that health services are effective at supporting breastfeeding in the postnatal period, but that beyond the 1-year review the focus shifts to rapid weaning. A new approach to support breastfeeding continuation alongside the introduction of complementary foods is needed in line with professional guidance and recommendations. As critical reflective practitioners, health visitors are ideally placed to support and educate women about the wider social complexities of breastfeeding. However, health service commissioners need to recognise the importance of investment in the profession to enable health visitors to use their skills fully.